Development of factors affecting the cost and income of hungarian broiler fattening between 1986 and 2014 - Jankovics, Péter (Studia Mundi – Economica, 2018)
Between 1980 and 2014 the efficiency of the Hungarian broiler production improved significantly, but there is a gap in international comparison. The broiler production cost shows a very tight correlation with the price of the day old chick, feed and energy. Between 1986 and 2014 only 98% of the production cost increase is reflected in the selling price, and that had an adverse effect to the income relations of the sector. There is a tight statistic correlation between the production indicators and the production costs expressed in real terms. The improvement of the efficiency affected the production cost positively, but it could not compensate the negative effects of the development of the input-output prices.